Qualidade da carne de borregos Santa Inês abatidos em diferentes pesos - Brito, Ingrid Rodrigues Sousa (2020)
The lack of standardization of meat products leads consumers to come across meats that differ in quality, noticeably altering the taste, appearance, aroma, softness and amount of fat. Such factors can vary according to race, sexual category, age and slaughter weight. Thus, the objective was to evaluate the physical, chemical and sensory parameters of meat of confined Santa Inês lambs, slaughtered at different weights. Twenty-four Santa Inês non-castrated male lambs were used, with initial mean age of 80 days and 16.52 ± 1.92 kg of initial body weight. The experimental treatments consisted in four slaughter weights (26; 32; 38 and 44 kg). The experimental design used was entirely random with four treatments and six repetitions. The parameters were pH, temperature at 45 min and 24 h after slaughter, moisture, protein, mineral and lipid contents, water holding capacity, cooking weight loss, shear force, color using L*, a* and b*, chroma, Hº, as well as the sensory attributes of taste, color, aroma and global acceptance. The initial meat temperature showed an increasing linear behavior as the slaughter weight increased, while the final temperature showed quadratic behavior. As the slaughter weight increased the initial pH showed quadratic behavior. With the rise of slaughter weight there was a linear increment in the lipid content of meat, with an increase of 0.33% for each kilogram in slaughter weight. The water holding capacity showed quadratic behavior when slaughter weight increased, the maximum value being 42.11% obtained in the slaughter weight of 35,13 kg by equation. Similarly, the cooking weight loss responded in a quadratic way to the increase in slaughter weight, with a minimum value of 34.84% observed with the slaughter at 34.55 kg by equation. The shear force showed an increasing linear behavior as the slaughter weight increased. With the increase of slaughter weight there was an increased linear behavior of pH measured after storage and thawing of meat. Luminosity and Hº decreased as the slaughter weight increased. The greatest juiciness was observed at 32 kg and the smallest at 26 kg, both were similar to 38 and 44 kg. The slaughter weight influences the physicochemical and sensory characteristics of Santa Inês lamb meat. The slaughter of Santa Inês lambs with approximately 35 kg is recommended, thus obtaining the most desired qualitative characteristics for the meat in terms of the lipid content, water holding capacity, weight loss by cooking, shear force, luminosity, Hue angle, hardness and juiciness.